The Effect of the Duit Model on Inductive Thinking among Second-Grade Students in Physics - Hassan, Raghad Falah (South Eastern European Journal of Public Health, 2024)
The research aims to identify the impact of the (Duit) model on the inductive thinking of students at the second intermediate level of physics. Randomly, the researcher chose the average of the daytime government girls in the Al-Saddah sub-district in Babil Governorate, as the school contains four divisions (A- B -C - D). In the drawing method, Division (A) was chosen to represent the control group that will study in the usual way, and Division (B) represents the experimental group that will study according to the (Duit) model in physics. The total number of female students after exclusion reached (74) students (38) for the experimental group and(36) for the control group. The researcher conducted a parity between the students of the two research groups for the following variables (chronological age calculated in months, previous information, Daniels intelligence test, inductive thinking test). The research was limited to the students of the second intermediate grade for the academic year (2023-2024) for the second semester and the specific scientific subject (fourth semester, fifth semester, sixth semester) of the physics textbook. After conducting the equivalencies between the two groups, the researcher prepared the application requirements for the two groups. After completing the experiment, the researcher applied her research tools to both groups as she obtained data and was processed by the t-test and the results showed the superiority of the experimental group in the control group according to the Duit model in inductive thinking.